In vitro reconstitution of temperature-dependent phosphorylation of DEHYDRATION-RESPONSIVE ELEMENT BINDING PROTEIN2A by Arabidopsis CASEIN KINASE 1 suggests a potential biochemical basis of thermal sensing - Fujii, Hiroaki (Springer Science and Business Media LLC, 2026)
Excessive and misregulated stress responses can negatively impact plant growth, highlighting the importance of mechanisms that enable the precise sensing of environmental cues such as temperature. Accurate temperature perception is essential for plant survival under fluctuating environments. DEHYDRATION-RESPONSIVE ELEMENT BINDING PROTEIN (DREB)2A, one of the key transcription factors in plant heat stress response, accumulates and becomes active under heat stress, whereas it is degraded under non-stress conditions. The degradation is triggered by phosphorylation, which is inhibited at 37 °C. However, no molecular thermosensor regulating DREB2A degradation has been identified. In this study, the temperature-dependent phosphorylation of DREB2A was reconstituted in vitro using recombinant proteins. Arabidopsis Casein Kinase 1 (CK1) phosphorylates DREB2A at 23 °C but not at 37 °C, reflecting the temperature dependency observed in vivo. The successful reconstitution indicates that no additional thermosensor is required for the temperature-dependent phosphorylation in vitro. Chimera analysis with human CK1 suggests that this temperature dependency is mediated by the middle domain of Arabidopsis CK1. Thus, Arabidopsis CK1 has the potential to function as a molecular thermosensor in DREB2A-mediated heat stress responses, although in vivo validation remains to be explored.